Expression of CD38 on Macrophages Predicts Improved Prognosis in Hepatocellular Carcinoma - Lam, Jian Hang; Ng, Harry Ho Man; Lim, Chun Jye; Sim, Xin Ni; Malavasi, Fabio; Li, Huihua; Loh, Josh Jie Hua; Sabai, Khin; Kim, Joo-Kyung; Ong, Clara Chong Hui; Loh, Tracy; Leow, Wei Qiang; et al. (Frontiers in Immunology, 2019)
CD38 is involved in the adenosine pathway, which represents one of the immunosuppressive mechanisms in cancer. CD38 is broadly expressed across immune cell subsets, including human macrophages differentiated in vitro from monocytes, but expression by tissue-resident macrophages remains to be demonstrated. We analysed tissue samples obtained from 66 patients with hepatocellular carcinoma (HCC) from Singapore and analysed using immunohistochemistry. Tumor-infiltrating leukocytes (TILs) were further examined using DEPArrayTM., and the phenotype of freshly isolated TILs was determined using flow cytometry. It is found that CD38 was frequently co-expressed with the macrophage-specific marker CD68. CD38+CD68+ macrophage density was associated with improved prognosis after surgery, while total CD68+ macrophage density was associated with poor prognosis. DEPArrayTM. analysis revealed the presence of large (>10 µm), irregularly shaped CD45+CD14+ cells that resembled macrophages, with concurrent CD38+ expression. Flow cytometry also revealed that majority of CD14+HLA-DR+ cells expressed CD38. In conclusion, CD38 expression was clearly demonstrated on human macrophages in an in vivo setting. The positive association identified between CD38+ macrophage density and prognosis may have implications for routine diagnostic work.